A Rare Case of Steroid-Resistant Neurosarcoidosis of the Cavernous Sinus With Optic Neuropathy: A Case Report. (October 2021) - Barforoshi, Shiva; Patel, Nikhil A.; Singh, Alvin P.; Li, Terrence; Mba, Benjamin
Sarcoidosis is an inflammatory disease that presents with nervous system involvement in 5-10% of cases, commonly known as neurosarcoidosis. 1 While there are no randomized controlled trials for the treatment of neurosarcoidosis, expert opinion supports initial treatment with corticosteroids and the use of steroid-sparing or anti-TNF agents in refractory or severe cases. We report a case of a 48-year-old African American male with a past medical history of biopsy-proven hepatic and renal sarcoidosis and progressive headache, dizziness, and blurry vision for 5 months, presenting with an acute exacerbation of right-sided vision loss over one day. MRI of the brain revealed a dural-based mass extending into the right cavernous sinus and compressing the right optic nerve. Given the pathological confirmation of systemic granulomatous disease consistent with sarcoidosis, clinical manifestations, bilateral hilar and mediastinal lymphadenopathy, MRI findings typical of central nervous system inflammation, and exclusion of other possible etiologies, the patient was diagnosed with probable neurosarcoidosis. Corticosteroids initially resolved his symptoms; however, he suffered an acute relapse. Combination therapy with corticosteroids plus mycophenolate mofetil (MMF) led to the eventual resolution of his symptoms. Only 8 cases of neurosarcoidosis involving the cavernous sinus have been reported. Our patient represents the only reported case of probable neurosarcoidosis of the cavernous sinus with optic neuropathy successfully treated with corticosteroid plus MMF combination therapy. We highlight the need to consider early, aggressive treatment in cases of neurosarcoidosis with optic neuropathy and to develop criteria to guide treatment strategy based on neurolocalization and the degree of neurological disability.